Disaggregate measures of corporate social performance and stock returns : a US perspective - Ang, Soon Heng (2013)
This paper examines the relationship between corporate social responsibility (CSR) and stock returns in the United States using disaggregated indicators of CSR from the KLD database including employee relations, environment, community, corporate governance, diversity, human rights and product. Our results review negative relationships between the indicators and stock returns, except for product and human rights, although only employee relations, environment and product indicator coefficients are statistically significant at at least the 5% level. Statistical significances are also found at the industry level, although results vary across the industries. In the consumer services industry, corporate governance, product and environment indicators were significant at at least the 5% level when regressed against both 1-year and 2-year returns. For the utilities industry, employee relations and product indicators were significant while only the corporate governance indicator was significant for the finance industry. In general, CSR is verified to have a negative relationship with stock returns, which are rationalised by prior literature, which explain that high CSR firms having a lower risk and stock demand, although the strength and significance of the relationship vary across industrial sectors.